Progress in the Application of Drugs for the Treatment of Multiple Sclerosis - Wei, Weipeng; Ma, Denglei; Li, Lin; Zhang, Lan (Frontiers in Pharmacology, 2021)
Multiple sclerosis (MS) is an autoimmune and chronic inflammatory demyelinating disease of the central nervous system (CNS), which gives rise to focal lesion in CNS and cause physical disorders. Although environmental factors and susceptibility genes are reported to play a role in the pathogenesis of MS, its etiology still remain unclear. At present, there is no complete cure, but there are drugs that decelerate the progression of MS. Traditional therapies are disease-modifying drugs that control disease severity. MS drugs that are currently marketed mainly aim at the immune system; however, increasing attention is being paid to the development of new treatment strategies targeting the CNS. Further, the number of neuroprotective drugs is presently undergoing clinical trials and may prove useful for the improvement of neuronal function and survival. In this review, we have summarized the recent application of drugs used in MS treatment, mainly introducing new drugs with immunomodulatory, neuroprotective, or regenerative properties and their possible treatment strategies for MS. Additionally, we have presented Food and Drug Administration-approved MS treatment drugs and their administration methods, mechanisms of action, safety, and effectiveness, thereby evaluating their treatment efficacy.